Long-Term Effects of Hearing Aids on Hearing Ability in Patients with Sensorineural Hearing Loss - Goel, Anurag R.; Bruce, Haley A.; Williams, Nicholas; Alexiades, George (Journal of the American Academy of Audiology, 2021)
Background A frequent concern surrounding amplification with hearing aids for patients with sensorineural hearing loss is whether these devices negatively affect hearing ability. To date, there have been few studies examining the long-term effects of amplification on audiometric outcomes in adults.Purpose In the present study, we examined how hearing aids affect standard audiometric outcomes over long-term periods of follow-up.Research Design We retrospectively collected audiometric data in adults with sensorineural hearing loss, constructing a model of long-term outcomes.Study Sample This retrospective cohort study included 802 ears from 401 adult patients with bilateral sensorineural hearing loss eligible for amplification with hearing aids at a single institution.Intervention Of the eligible patients, 88 were aided bilaterally, and 313 were unaided.Data Collection and Analysis We examined the standard three-frequency pure-tone average (PTA3-Freq), a novel extended pure-tone average (PTAExt), and word recognition score (WRS) per-ear at each encounter. We then modeled the association between the use of hearing aids for 5 years and these audiometric outcomes using targeted maximum likelihood estimation.Results In comparing aided and unaided ears at the end of 5 years, there were discernible effects for all measurements. The PTA3-Freq was 5 dB greater in aided ears (95% CI: 1.37–8.64, p = 0.007), WRS was 4.5 percentage points lower in aided ears (95% CI: −9.14 to 0.15, p = 0.058), and PTAExt was 5 dB greater in aided ears (95% CI: 2.18–7.82, p < 0.001), adjusting for measured confounders.Conclusion Our analysis revealed discernible effects of 5 years of hearing aid use on hearing ability, specifically as measured by the PTA3-Freq, novel PTAExt, and WRS, suggesting a greater decline in hearing ability in patients using hearing aids. Future studies are needed to examine these effects between treatment groups over longer periods of time and in more heterogeneous populations to improve clinical practice guidelines and safety of both prescriptive fitting nonprescriptive amplification.
Keywords: sensorineural hearing loss; hearing aid; long-term effects; pure-tone average; word recognition; hearing ability; adverse effect